Biologically Uninspired Computer Science. - Teuscher, Christof (Communications of the ACM, 2006)
The article focuses on metaphors in computer science. Computer science has remained largely unchanged since the 1940s, the author argues. The author argues that while biology is a useful metaphor in computer programming, it has some limitations. New types of metaphors might be useful in order to reach the goal of building more life-like computers. One of the possibilities that the author suggests is art. The author also discusses why it is dangerous to imitate living things too closely; the example of airplane wings, which are fixed, and a bird's wings, which flap, is given.